Conservation concerns a guide for collectors and curators - Bachmann, Konstanze (Smithsonian Institution Press, 1992)
Written in accessible, nontechnical language, this book's twenty-three essays provide invaluable conservation guidelines for a variety of materials and media. Focusing also on proper storage techniques and environmental control, contributors offer information on emergency planning, disaster management, and identifying damages that may require professional treatment.